Motif Penyelenggaraan Pendidikan Islam dan Implikasinya pada Pola Manajemen dan Kepemimpinan - Mahmud, Muchammad Eka (Dinamika Ilmu, 2012)
In individual and organizational manner, society has a motivation to establish Islamic education (Pondok Pesantren/ madrasah/ school) in order to meet their needs of education. As a matter of fact, it can be found that the school is built in limited resources. They are supported by the high level of religious spirit. Based on its quantity, percentage of those schools are over than 90% that belong to the society. The rest of them is 10% belong to the government which is categorized as a state school. Spirit of Islamic society to establish educational institution is supported by several things such as, Islamic teaching motive, preservation of parental beneficiary, strengthen of organization (regeneration of human resources empowerment), competition of influence, social demand, messages from the public figures and science development motive. This educational institution establishment motive is certainly has an implication to management and leadership pattern such as management of the institution which is tradition based instead of professional manner based on particular skills such as human skill, conceptual skill, and also technical skills in integrated way. As a result, there is no any fixed plan and also distribution of power equally. Implementation of Islamic education in any motive will get stagnant if it is not professionally and innovatively done. The institution will be exist if there is a change, innovation, professional management, accountability of financial statement, and human resources empowerment. It is necessary for Islamic education institution to have a future oriented thought in order to improve quality of the institution instead of their own group, tribes, and belief.